Implementation of Rural Infrastructure Development in Pohuwato Regency - Gretty Syatriani Saleh (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
This study aims to determine the role of the village government in improving the welfare of the people of Bulili Village, Duhiadaa District, Pohuwato Regency. The research approach uses descriptive research. Informants were the village head, village head, BPD chairman, LPM Chair, village treasurer and Bulili village community leaders. The results showed that the Bulili Village Government in improving community welfare carried out three programs such as: 1) an increase in agricultural production programs planning assistance that would improve the economy of Bulili villagers such as providing rice seeds, corn seeds, tractor assistance, hansplayer assistance (tengki), assistance fertilizer, and PNPM assistance, 2) program to increase livestock production, namely the collaboration of district governments, sub-district governments and village governments in the form of providing assistance for productive superior cow and productive goat seeds to cattle farmers in the Bulili village community formed by Bulili village government . 3) development of village livestock agribusiness, which is to form a group of livestock farmers who are given the assistance of productive cow and goat seeds to each group to be managed.